A Multicriteria Approach for Measuring Employee Well-Being - Junjie Dong; Shumin Yan (Frontiers in Psychology, 2022)
This paper proposes that employee well-being includes four dimensions: job satisfaction, life satisfaction, positive affect, and negative affect. Each dimension is interdependent and correlated. Therefore, the measurement of employee well-being is complicated and fuzzy. This study aims to treat the measurement of employee well-being as a fuzzy problem, construct a measurement model from the perspective of multi-criteria decision making, and establish the preference relationship between indicators through fuzzy measure and Choquet integral. Applying multiple linear regression analysis and the heuristic least mean squares method, the main findings are as follows: (1) It is inappropriate to use job satisfaction as a substitute for measuring employee well-being, as the weight of job satisfaction is the lowest among the four dimensions. (2) Employee well-being is also largely reflected in their overall satisfaction with life because life satisfaction is the most heavily weighted. (3) Employee well-being needs to consider the emotion-related indicators and satisfaction-related indicators comprehensively because fuzzy analysis proves that their relationship is redundant. Finally, the practical implications of these findings and future research directions are discussed.